(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
استُخدمت طريقة القص المائل (Inclined shear) في هذه الدراسة بوصفها طريقةً أوليّة من طرائق إزالة التشوهات التكتونية (Restoration)، وذلك بهدف إزالة الإزاحة الناتجة عن تأثير الفوالق العادية التي تشكلت بفعل القوى التكتونية الشدّية التي ضربت منطقة الورد. إذ طُبقت هذه الطريقة باستخدام برنامج 2D moveعلى المقطع السيزمي العمقي Inline A 2157)) ذي الاتجاه شمال شرق- جنوب غرب، وعلى امتداد منطقة الدراسة. في حين استُخدمت طريقة القص الشاقولي (Vertical shear) بوصفها طريقةً مكمّلة بهدف إزالة التشوهات التكتونية نهائياً، وتحديدًا للتشكيلات الواقعة تحت سطح عدم توافق قاعدة الكريتاسي المتأخر (BKU) المتضمنة تشكيلات الخابور والضبيات والمولوساF والرطبة. أسهمت طريقتا القص المائل والقص الشاقولي؛ أو طريقة الإعادة إلى المرجع (Restore to datum)، في بناء مقاطع جيولوجية عدة مثّلت التغيرات التكتونية لمنطقة الدراسة بدءاً بالأردوفيسي الأعلى، وانتهاءً بالزمن الحالي. The inclined shear restoration technique was used in this research as the primary method to remove the effects of fault displacements. These displacements were resulted from the impact of the NE-SW trending extensional forces. The inclined shear restoration technique was applied to the NE-SW trending seismic section (Inline A2157) along the Elward Area, using 2D move software. The vertical shear restoration technique was used as a complementary method to remove the effects of folding associated with faulting, especially to formations under the Base Upper Cretaceous Unconformity (BKU). The inclined shear and the vertical shear restoration techniques contributed to build many geological sections according to depth seismic section (Inline A 2157). These sections showed the Tectonic setting of the study area from Upper Ordovician till current time.